STRATEGI KOMUNIKASI PEMASARAN TERPADU DINAS PARIWISATA DAN KEBUDAYAAN KABUPATEN SOLOK SELATAN DALAM MEMPROMOSIKAN PARIWISATA DAERAH - Ayu Widya; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Tourism is one of the potential resources that can be developed by each region. Tourism is also a potential sector to become one of the sources of local revenue (PAD). South Solok Regency holds a lot of potential for natural, cultural and historical tourism. In recent years tourist objects in the South Solok Regency began to become one of the favorite destinations of the people in West Sumatra. The popularity of some of these tourist objects is inseparable from the efforts of the Department of Tourism and Culture of South Solok Regency in conducting promotional efforts to introduce the potential of the South Solok Regency. This study aims to explain the integrated marketing communication strategy carried out by the Department of Tourism and Culture of South Solok Regency in promoting regional tourism.This research uses a qualitative method with the type of descriptive research. The collection of informants in the study usingtechniques purposive with the number of research informants as many as seven (7) people. The informants in this study were five employees of the Department of Tourism and Culture of South Solok Regency and two visitors of one of the leading tourist attractions in South Solok Regency. Data collection techniques consist of in-depth interviews, observation, and documentation. An interactive data analysis technique for Miles and Huberman. To achieve the validity of the data in this study, the authors used an extension of participation and triangulation.The results of this study indicate that the Department of Tourism and Culture of South Solok Regency implemented an integrated marketing communication strategy as an effort to promote regional tourism. There are five promotional mixes used are as follows: (1) Advertising using print media, electronic media and outdoor media, (2) Sales Promotion is carried out by participating in exhibitions and conducting tourism events, (3) Personal Selling by cooperating with associations tourism and travel agents in offering tour packages, maximizing the role of guides, and making the Tourism Ambassador Uda as an icon of tourism as a liaison between the government and the community, (4) Social Media Marketing by using websites and social media as promotional media, (5) Public Relations & Publicity The Office of Tourism and Culture establishes good relations with stakeholders, the media and the community.